Rethinking the sexual offenses exception to previous consistent statements: An evaluation of sections of 58 and 59 of SORMA. - Mesthrie, Sapna (Department of Public Law, 2023)
This dissertation examined whether the rules contained in sections 58 and 59 of the Criminal Law (Sexual Offences and Related Matters) Amendment Act 32 of 2007 (SORMA) could be reconciled with the aims and objectives of the legislation. It also considered whether these rules improved the position that previously existed under the common law. These provisions enable the first report made by a complainant in a sexual offence matter to be admitted into evidence at trial and constitute a statutory exception to the general rule that previous consistent statements are inadmissible. The methodology adopted in this investigation was a desktop review of secondary literature and reported cases. This dissertation analysed case law relating to the common law exception which existed prior to the enactment of SORMA and case law following the implementation of SORMA. This analysis makes it clear that the common law sexual offences exception was based on antiquated and misogynistic thinking about sexual offences and the behaviour of women. This dissertation ultimately determined that SORMA has not had the desired impact of reforming the common law on prior complaints as envisioned by the drafters. Instead, the analysis indicates that the undesirable common law position has been codified. It is argued that this can be attributed, in part, to the ambiguous drafting of sections 58 and 59 which do not clarify whether the prior complaint must have been made at the first reasonable opportunity, as was required under the common law. The analysis of case law demonstrates that this uncertainty has led to the timing of a complaint often being a central issue in sexual offence cases. This further perpetuates the anomaly which existed under the common law. This dissertation concludes that the failure by the legislature to expressly abolish the common law requirement that a prior complaint be made at the first reasonable opportunity is not congruent with the aims and objectives of SORMA. It is recommended that SORMA be amended to include an express provision that prior complaints in sexual offence cases are admissible regardless of the timing of the complaint. This would ensure that legal reform corresponds with social science evidence on the psychology of rape and the difficulties of disclosure.